Incorporating gender perspective in small environmental projects. The experience of El Almanario in ten indigenous communities in Guatemala - Lopez-Torrejon, Estela; Boni-Aristizábal, Alejandra; Peris-Blanes, Jordi (Iberoamerican Journal of Development Studies, 2012)
The Almanario is a project management methodology created by Small Grants Programme in Guatemala which operates following United Nations Global Environment Fund premises. The main goal of our research is to show the results of fourth compulsory gender measures included in the Almanario approach in ten indigenous communities in Western Guatemala. The research reveals women participation has been increased and had allowed them to manage project resources. Two measures (the Promotora role and mixed Advisory Board) are preliminary steps to visualize women leadership but more time is needed in order to consolidate and increase women participation. Nursemaids are perceived by women as a good measure to increase participation and really appropriate in a patriarchal context. Gender and self-esteem trainings have increased women self-esteem and awareness on women rights. CITE AS: López-Torrejon, E., Boni-Aristizabal, A., Peris-Blanes, J. (2012). Incorporando la perspectiva de género en pequeños proyectos ambientales. La experiencia del Almanario en 10 comunidades indígenas de Guatemala. Iberoamerican Journal of Development Studies, 1 (1): 84-100